Protective Efficacy of the Calicivirus Valency of the Leucofeligen Vaccine against a Virulent Heterologous Challenge in Kittens - Cynthia Lesbros; Virginie Martin; Wojciech Najbar; Annaele Sanquer; David Mcgahie; Hyone-Myong Eun; Sylvie Gueguen (Veterinary Medicine International)
Feline calicivirus (FCV) is a common feline pathogen with a potential for antigenic diversity. This study aimed to evaluate and characterize the protective efficacy of the FCV-F9 valency of a tetravalent vaccine, Leucofeligen, against challenge with an unrelated strain. Ten 9-week-old kittens were vaccinated while 10 remained as unvaccinated controls. The vaccinated cats received Leucofeligen twice subcutaneously with a 3-week interval. Four weeks after the second vaccination, all cats were challenged with virulent heterologous FCV and followed up for 21 days, monitoring their general condition, clinical signs, and immunological responses. During the vaccination phase, rectal temperatures and body weights were indistinguishable between the two groups. Only vaccinated cats showed FCV-specific seroconversion (both total and neutralizing antibodies). In the first week after challenge, the vaccinated cats had an 82.6% reduction in median clinical score compared to controls. Leucofeligen was thus shown to provide a significant clinical protection to kittens challenged with heterologous virulent FCV. This protection was similar whether the cats had neutralizing antibody or not, indicating a key role for cellular immunity in the overall protection. This also suggests that previously reported seroneutralisation studies may underestimate the level of cross-protection against field strains obtained with this modified live FCV-F9 vaccine.